Prevalence of diabetes foot ulcers and associated factors among adult diabetic patients in three referral hospitals in Mogadishu, Somalia - Salad, Abdulwahab M.; Duale, Hodan A.; Sheikh, Ismael M.; Hassan, Gallad Dahir; Farah, Abdiqani A.; Gele, Abdi (Frontiers in Public Health, 2023)
Background: Diabetes mellitus (DM) causes significant morbidity and mortality in sub-Saharan Africa (SSA) including Somalia. Among diabetic patients, diabetic foot ulcers (DFUs) constitute the largest proportion of admissions, amputations and mortality. The aim of this study is to assess the prevalence of diabetic foot ulcers and subsequently determine factors associated with it among diabetic patients at three major hospitals in Somalia. Methods: An institutional-based cross-sectional study was conducted among 193 diabetic patients between August and November 2022. All eligible diabetes patients who were attending at De Martini Hospital, Madina General Hospital, and Deynile General Hospital during the study period were included in the study. Patients were interviewed using a structured questionnaire. We collected demographic, clinical and behavioral variables from all participants. Data completeness was checked in Excel and then data were exported to SPSS version 20 for analysis. Descriptive statistics including frequencies and percentages were presented to describe participants' characteristics. Bivariate and multivariable logistic regression analysis was carried out to examine association between number of potential risks with the outcome variable. Odds ratio with 95% confidence interval (CI) were reported. Result: Mean age of the study’s participants was 50.9±13.6 years. The prevalence of diabetic foot ulcer was 15 %. Patients who were either overweight or obesity (OR 4.63, CI: 2.08 - 10.30), lack of family support in managing diabetes (OR 3.33, CI: 1.74 - 6.36), and not checking feet regularly were more likely to develop DFUs (OR 1.99, CI:1.08 - 3.66). Conclusion: Increased body mass index, lack of family support, and not checking feet regularly were associated with DFUs. The high prevalence of DFUs and the plethora of needs of people with DFU pose challenges for health care. A coordinated health care system is necessary to meet the needs of diabetic patients and to prevent DFUs.